The relationship between ACTN3 R577X gene polymorphism and physical performance in amateur soccer players and sedentary individuals - Fatma E. Koku; Süleyman O. Karamızrak; Aynur S. Çiftçi; Hasan Taşlıdere; Burak Durmaz; Özgür Çoğulu (Termedia Publishing House, 2018)
The aim of this study was to determine the distribution of ACTN3 R577X gene polymorphism in soccer players and sedentary individuals, and to investigate the relationship of this distribution with performance tests. A total of 100 soccer players and 101 sedentary individuals were enrolled in the study. Standing long jump and countermovement jump (with arm swing, without arm swing and repeated) scores were recorded, using a jump meter. Maximum VO 2 levels were measured using a treadmill-connected cardiopulmonary exercise device, Masterscreen CPX. ACTN3 R577X polymorphism was evaluated by real-time PCR. ACTN3 R577X genotype distribution was found to be similar in soccer players and controls (p>0.05). The only statistically significant finding was a shorter countermovement jump with arm swing scores in the RR-genotyped soccer players, compared with their RX genotyped counterparts (p<0.05). In the soccer player group, RX-genotyped subjects were observed to have lower respiratory threshold values compared with RR-genotyped subjects (p<0.05). No significant correlation was detected between this distribution and performance test results. ACTN3 R577X genotype distribution was found to have no effect on sprint and endurance characteristics in amateur soccer players. The ACTN3 R577X polymorphism may not be a specific enough genetic marker to determine athletic performance in soccer.